The resistance to change in implementation of total quality management (TQM) in Iranian schools. Issue 5 (10th August 2015) - Pourrajab, Masoumeh; Basri, Ramli; Daud, Shaffe Mohd; Asimiran, Soaib
Abstract : Purpose: – The purpose of this paper is to identify the level of resistance to change in implementation of total quality management (TQM) in Iranian schools and investigate the influence of principals' and teachers' gender and years of experience on resistance to change. Design/methodology/approach: – This study presents the results of survey research carried out in Iran. The participants of this study are secondary school principals and teachers. The researchers employed descriptive analysis on data collected. Independent sample t -test was used to determine the difference in resistance to change based on teachers and principals gender, and one-way ANOVA and Kruskal-Wallis H -test were applied to determine the difference in resistance of teachers and principals based on years of experience. Findings: – The researchers found that the level of resistance to change in Iranian schools is medium; the most important factor for resistance to change is confidence in the status quo. Gender has an effect on resistance to change only for teachers. Years of experience do not have an effect on resistance to change. Originality/value: – The study identifies some useful points for school's principals and teachers to implementation of TQM in school.